Tax Revenue Trends in Latin America and Asia: A Comparative Analysis. Issue 2 (26th January 2019) - Aizenman, Joshua; Jinjarak, Yothin; Kim, Jungsuk; Park, Donghyun
ABSTRACT: We take stock of and compare tax revenue trends in Latin America and Asia. The tax revenues to GDP ratios increased significantly in both regions in the 2000s, although they remain visibly below European levels. Our analysis portrays a complex picture of the tax collection challenges facing developing countries. Overall, there remains sizable heterogeneity in the revenue performance of developing countries, and across regions. While progress had been constructed, the gap between the advanced economic systems and developing countries suggests ample room for future fiscal developments, and for more disaggregated studies of the tax mobilization challenges facing developing countries in the wake of the worldwide fiscal crisis.